A Phase I Clinical Study of the Pharmacokinetics and Safety of Prusogliptin Tablets in Subjects with Mild to Moderate Hepatic Insufficiency and Normal Liver Function - Zhang, Huiting; Bian, Yicong; Zhao, Weifeng; Miao, Liyan; Zhang, Hua; Cui, Juanjuan; Zhang, Xiaofang; Zhang, Xueyuan; Cai, Wen (Current Drug Metabolism, 2024)
Background: Prusogliptin is a potent and selective DPP-4 inhibitor. In different animal models, Prusogliptin showed potential efficacy in the treatment of type 2 diabetes. However, the knowledge of its pharmacokinetics and safety in patients with liver dysfunction is limited. Objectives: The present study evaluated the pharmacokinetics and safety of Prusogliptin in subjects with mild or moderate hepatic impairment compared with healthy subjects. Methods: According to the liver function of the subjects, we divided them into a mild liver dysfunction group, a moderate liver dysfunction group and a normal liver function group. All subjects in three groups received a single oral dose of Prusogliptin 100-mg tablets. Pharmacokinetics and safety index collection was carried out before and after taking the drug. Plasma pharmacokinetics of Prusogliptin were evaluated, and geometric least- -squares mean (GLSM) and associated 90% confidence intervals for insufficient groups versus the control group were calculated for plasma exposures. Results: After a single oral administration of 100 mg of Prusogliptin tablets, the exposure level of Prusogliptin in subjects with mild liver dysfunction was slightly higher than that in healthy subjects. The exposure level of Prusogliptin was significantly increased in subjects with moderate liver dysfunction. There were no adverse events in this study. Conclusion: The exposure level of Prusogliptin in subjects with liver dysfunction was higher than that in healthy subjects. No participant was observed of adverse events. Prusogliptin tablets were safe and well tolerated in Chinese subjects with mild to moderate liver dysfunction and normal liver function.
Keywords: hepatic impairment